مستوى أداء مدرسات مادة الاحياء على وفق تكنولوجيا المعلومات وعلاقته بتحصيل طالباتهن (Journal of the College of Basic Education, 2023)
The objective of the current research is to identify the level of performance of female biology teachers according to information technology and its relationship to the achievement of their students. of their female students by (30) female students for each teacher, and the researcher used a tool to measure the teaching skills according to information technology among the members of the research sample, as it was represented by the observation card (45) paragraphs were presented to a group of arbitrators, and their psychometric characteristics were extracted. The achievement test was used to measure the achievement of female students, as the number of its paragraphs reached (50) multiple-choice items. It was presented to the arbitrators and its validity and reliability were confirmed. A group of statistical methods were used, including the test The t-test for one sample, Pearson's correlation coefficient, and the Kron-Bach alpha equation. The results showed the availability of teaching skills according to information technology among the teachers of the research sample. The research came out with a set of recommendations and proposals.